Organizational Performance Analysis Of The Bengkulu VII Sumatera River Regional Area - Deky Agusprawira; Slamet Widodo; Kamaludin Kamaludin (The Manager Review, 2023)
This study aims at the performance of the Sumatra VII Bengkulu River Basin Center in terms of the availability of water resources infrastructure and the quality of organizational governance. This type of research uses qualitative descriptive approach research with survey methods. In this study, the authors collected information data and basic information using disseminated questionnaires, interviews and documentation studies. The data to be used in this study is primary data obtained directly from respondents of ASN employees of the Sumatra VII River Basin Center Bengkulu totaling 163 people. Data analysis methods are used, descriptive analysis and qualitative analysis. The results showed that (1) The achievement of the organizational performance of the Sumatra VII Bengkulu River Basin Center in the aspect of providing water resources infrastructure was already in the very high category (AA). The results illustrate that the strategic work program for the provision of water resources infrastructure has been fully implemented; and (2) The achievement of organizational performance of the Sumatra VII River Basin Center Bengkulu from the aspect of the quality of organizational governance is already in the high (AB) and very high (AA) categories. The results illustrate that the quality of organizational governance quality strategic work programs have been implemented and some others are still not optimal. Keywords: Performance, Water Resources Infrastructure and Quality of Governance